2011
DOI: 10.1017/s1368980011002965
|View full text |Cite
|
Sign up to set email alerts
|

Is dieting behaviour decreasing in young adolescents?

Abstract: Objective: To report trends in underweight, overweight and obesity in 12-15-year-old adolescents and examine changes in dieting behaviour, which have been less well documented. Design: Comparison of two independent representative cross-sectional surveys. Setting: Northern Ireland. Subjects: Weight and height were objectively measured in 1324 boys and 1160 girls in 1996 and 1274 boys and 1374 girls in 2007. Participants reported whether they were following any particular diet including a self-proposed or prescr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 48 publications
1
1
0
Order By: Relevance
“…The present results also showed that adolescents who were dieting at the time of the survey or who had dieted in the past had significantly higher BMI and body fat percentage than those who had never dieted, in both sexes. These results are consistent with other findings showing that overweight and obese individuals will more often engage in dieting in order to control their weight than normal-weight individuals ( 6 , 34 , 35 ) . However, dieting has been shown to be prevalent among normal-weight adolescents as well; and it has been related to self-perceived weight status and body image distortion ( 36 ) .…”
Section: Discussionsupporting
confidence: 93%
“…The present results also showed that adolescents who were dieting at the time of the survey or who had dieted in the past had significantly higher BMI and body fat percentage than those who had never dieted, in both sexes. These results are consistent with other findings showing that overweight and obese individuals will more often engage in dieting in order to control their weight than normal-weight individuals ( 6 , 34 , 35 ) . However, dieting has been shown to be prevalent among normal-weight adolescents as well; and it has been related to self-perceived weight status and body image distortion ( 36 ) .…”
Section: Discussionsupporting
confidence: 93%
“…Whittle et al (51) reported trends in underweight, overweight and obesity among young adolescents in Northern Ireland for the period 1996 to 2007. Their data illustrated rising rates of overweight and obesity among low and high obesity reviews SEP children.…”
Section: Northern Irelandmentioning
confidence: 99%